EFEKTIFITAS BATAS USIA PERKAWINAN DAN DISPENSASI PERKAWINAN (PASAL 7) UU NO 16 TAHUN 2019 TENTANG PERUBAHAN UU NO 1 TAHUN 1974 (Studi Di Pengadilan Agama Kabupaten Malang) - valeriel margarettha susanto (Dinamika, 2021)
ABSTRACT The new marriage age limit is stipulated in Law No. 16 of 2019 amendments referring to article 7 which states that the age limit of both men and women is the same as 19 years. But judging from the cases of marriage dispensation applications in january to March of 2019 reached 113 cases which means there are still many early marriages. Therefore, the author examined the effectiveness of marriage age limit and marriage dispensation article 7 of Law No. 16 of 2019 on the amendment of Law No. 1 of 1974 research conducted in the Malang Regency Religious Court. This type of empirical research, sociological approach. The data obtained are primary and secondary data. qualitatively analyzed. The results of the study are the driving factors of people applying for marital dispensation are: Factors of pregnant out of wedlock, economic factors, educational factors and social media as well as the effectiveness of the application of the new marriage age limit rules are still not effective because in reality the increase in the number of marriage dispensation in Pengadilan Agama Kabupaten Malang is creasingly.Key Words : Early marriage, Effectiveness, Marriage Dispensation  ABSTRAK Batas usia perkawinan yang baru diatur dalam UU No 16 Tahun 2019 perubahan mengacu pada pasal 7 yang menyatakan bahwa batas usia pria maupun wanita ialah sama 19 tahun. Namun dilihat dari kasus permohonan dispensasi kawin pada bulan januari sampai maret tahun 2019 mencapai 113 perkara yang artinya masih banyak terjadi perkawinan dini. Untuk itu penulis meneliti efektifitas batas usia perkawinan dan dispensasi perkawinan pasal 7 UU No 16 Tahun 2019 tentang perubahan UU No 1 tahun 1974 penelitian dilakukan di Pengadilan Agama Kabupaten Malang. Jenis penelitian empiris, pendekatan sosiologis. Data yang diperoleh ialah data primer dan sekunder. dianalisis secara kualitatif. Hasil penelitian yaitu faktor pendorong masyarakat mengajukan dispensasi kawin ialah: Faktor hamil diluar nikah, faktor ekonomi, Faktor pendidikan dan Media sosial serta efektifitas mengenai penerapan aturan batas usia perkawinan yang baru masih belum efektif karena pada realitanya kenaikan jumlah perkara dispensasi perkawinan di Pengadilan Agama Kabupaten Malang semakin banyak.Kata Kunci : Perkawinan Dini, Efektifitas, Dispensasi Perkawinan